Exploring the Efficacy of Plain English to Measure Legal Aspirants’ Comprehension of Judicial Judgments - Rubab, Iram; Batool, Ifra; Sahar, Yaghsha (Annals of Human and Social Sciences, 2022)
This study attempts to measure the linguistic adequacy of law students with reference to comprehension of judicial judgments and consumption of time. Data is collected in the form of test from the law students. Two tests are constructed comprising of five statements concerned with civil judicial judgments. Test 1 was carrying the original chunks of civil judicial judgments and test 2 was carrying the same test in plain version. Starting and ending of Timings were also essential to mention on the test. Tests were given to the 250 law students of five prestigious universities of Pakistan. The findings of the study revealed that the law students take less time while reading the plain legal language and raised the comprehensibility of judicial judgments.